The effect of Islamic work ethic on organizational justice - Rokhman, Wahibur; Hassan, Arif (2011)
The study proposed to investigate the effect of Islamic work ethic on justice perception among employees in Islamic microfinance institutions in Indonesia. The construct of organizational justice included three dimensions, namely, distributive, procedural, and interactional justice. The samples were drawn from 370 employees from 60 Islamic microfinance institutions in Central Java, Indonesia. The results suggested that Islamic work ethic positively contributed to the three dimensions of justice perception. Implication, limitation and suggestion for future research are discussed.